Business Incubator and Incubatee: A Thematic Review of Challenges and Success in Africa - Shillie, Peter Ngek; Wokwen, Cordelia (Universitas Islam Indonesia, 2024)
Business incubation has been widely promoted across Africa as a mechanism to stimulate entrepreneurship, generate employment, and reduce poverty; however, the outcomes of many incubation programs remain below expectations. This study aims to identify and synthesize the constraints that limit the effectiveness of business incubation, with particular attention to the perspectives of both incubators and incubatees. Employing a thematic literature review of thirty-six peer-reviewed sources retrieved from major academic databases, the analysis organized evidence into incubator-level and incubatee-level factors. At the incubator level, recurring challenges include limited staff competencies, unstable funding, inadequate governance structures, insufficient facilities, weak inter-incubator collaboration, policy friction, and sustainability risks. At the incubation level, barriers are manifested in low commitment, restricted access to technical facilities and workspaces, funding obstacles, and fragile peer networks. Networking has consistently emerged as a pivotal mechanism for overcoming resource scarcity and building collaborative capacity. The findings suggest that incubation outcomes are shaped not only by the resources and skills of incubators but also by the engagement and networking capabilities of incubatees. The study concludes that the underperformance of business incubation in Africa results from multiple interacting bottlenecks, highlighting the importance of professional capacity building, robust governance, financial stability, and the institutionalization of networks to improve entrepreneurial outcomes. By integrating fragmented evidence into a two-actor framework, this research contributes to the incubation literature and offers practical guidance for policymakers and program managers seeking to strengthen entrepreneurial ecosystems in resource-constrained environments.